Le Dernier des Injustes - Lanzmann, Claude (France, 2013)
In 1975 Lanzmann filmed a series of interviews with Benjamin Murmelstein, the last President of the Jewish Council in the Theresienstadt ghetto in Czechoslovakia, the only Elder of the Jews not to have been killed during the war. From Nisko in Poland to Theresienstadt, and from Vienna to Rome, the film provides an unprecedented insight into the genesis of the Final Solution. It reveals the true face of Eichmann, and exposes without artifice the savage contradictions of the Jewish Councils.
Verzio Film Festival Submission
Keywords: Documentary films